KUS121, an ATP regulator, mitigates chorioretinal pathologies in animal models of age-related macular degeneration. Issue 5 (May 2018) - Muraoka, Yuki; Iida, Yuto; Ikeda, Hanako O.; Iwai, Sachiko; Hata, Masayuki; Iwata, Takeshi; Nakayama, Mao; Shimozawa, Nobuhiro; Katakai, Yuko; Kakizuka, Akira; Yoshimura, Nagahisa; Tsujikawa, Akitaka
Abstract: Age-related macular degeneration (AMD) is a leading cause of blindness among elderly people. The appearance of drusen is a clinical manifestation and a harbinger of both exudative and atrophic AMD. Recently, antibody-based medicines have been used to treat the exudative type. However, they do not restore good vision in patients. Moreover, no effective treatment is available for atrophic AMD. We have created small chemicals (Kyoto University Substances; KUSs) that act as ATP regulators inside cells. In the present study, we examined the in vivo efficacy of KUS121 in C-C chemokine receptor type 2-deficient mice, a mouse model of AMD. Systemic administration of KUS121 prevented or reduced drusen-like lesions and endoplasmic reticulum stress, and then substantially mitigated chorioretinal pathologies with significant preservation of visual function. Additionally, we confirmed that long-term oral administration of KUS121 caused no systemic complications in drusen-affected monkeys. ATP regulation by KUSs may represent a novel strategy in the treatment of drusen and prevention of disease progression in AMD.